Histogram‐bin‐shifting‐based reversible watermarking for colour images. Issue 2 (1st March 2013) - Naskar, Ruchira; Subhra Chakraborty, Rajat
Abstract : Histogram‐bin‐shifting has been previously shown to be an effective method of reversibly watermarking greyscale images. For colour image reversible watermarking, histogram‐bin‐shifting technique can be extended trivially to RGB colour space. However, direct application of histogram‐bin‐shifting to the RGB colour image components, results in relatively poor performance of the watermarking algorithm. In order to improve the performance of the algorithm in terms of embedding capacity and distortion whereas preserving the inherent computational simplicity of the histogram‐bin‐shifting technique, the authors propose a technique of shifting frequency histogram bins of transformed colour components. In this study, the authors consider the YCbCr colour‐space. Experimental results on standard test images, prove that the proposed technique achieves high embedding capacity with considerably low distortion.